(untitled) (Submission and Review of Research -Biological Sciences Series, 2025)
The experiment was conducted in Al-Duruqiyat Village, Latakia Governorate, and in Latakia University Laboratoies during the agricultural season 2023 to study some morphological characteristics of sesame plants under the influence of five levels of phosphate fertilization (0, 40, 60, 80, 100) kg Tri Super Phosphate TSP: Ca(H2PO4)2. H2O (46% P2O5) / ha, and four concentrations of zinc spraying (0, 30, 60, 90) mg Zn2SO4 / l. The experiment was laid out in a Randomized Complete Block Design (R.C.B. D), with a single plot arrangement and three replicates. The results showed that the level of 100 kg Tri Super Phosphate TSP: Ca(H2PO4)2. H2O (46% P2O5) /ha was significantly superior to all other levels in all studied characteristics, and the spray concentration of 60 mg Zn2SO4/l gave the highest value of plant height and stem diameter, while the concentration of 90 mg Zn 2SO4/l gave the highest value of number of branches and number of leaves. The intervention of (100 kg Tri Super Phosphate TSP: Ca(H2PO4)2. H2O (46% P2O5) / ha x 60 mg Zn2SO4/ l) achieved significant superiority with plant height (142.67 cm), stem diameter (12.27 mm), and the height of the first capsules above the ground (20.44 cm). while the intervention of (100 kg Tri Super Phosphate TSP: Ca(H2PO4)2. H2O (46% P2O5) /ha x 90 mg Zn2SO4/ l) achieved significant superiority with number of branches (5 branches/plant) and number of leaves (168.90 leaves/plant).